UNDERSTANDING FORM–FUNCTION RELATIONSHIP: THE CASE OF WRITTEN TEXTS OF AN ELECTRONICS MANUFACTURING FIRM (Sains Humanika, 2009)
Writing documents for the workplace differs from that for an academic setting. Although much has been researched about meeting the needs of employers and employees; there is, yet, adequate research and thick descriptions to inform readers about how participants in the workplace negotiate meaning and how texts play a role in that respect. It has been argued that apart from knowledge of audience, purpose and mechanics of writing, the writer in the workplace should also be aware of the work culture of the organization he is in. Shared values, beliefs, expectations, norms and language are believed to have an influence in the shaping of texts. Each organization, it is said, to has its own specific set of goals and cultures; and texts are said to have had a role in the fulfillment of those goals. This attempt is part of a larger study, grounded in ethnography, aimed at examining texts and the role they play in realising the shared goals. The case in study was a Japanese multinational plant involved in car audio assembly. The objective was to gain insights into how texts are being shaped to meet the specific functions they were called on to serve; as well as how they shape the community’s behaviour. The texts were being analysed for content, type and form. Results indicate the meeting of quality standards, and effective and efficient execution of tasks through the writer’s deep awareness of the interplay of participant, shared purpose, shared beliefs, shared expectations and limitations in the environment.
Keywords: Writing texts; quality and efficiency of product and process; shared symbols; shared goals; shared values